Recycling ceramic waste powder: effects its grain-size distribution on fresh and hardened properties of cement pastes/mortars formulated from SCC mixes. Issue 3 (4th May 2019) - Ferrara, Liberato; Deegan, Peter; Pattarini, Andrea; Sonebi, Mohammed; Taylor, Su
Abstract : This article presents the results of a preliminary study assessing the feasibility of using waste ceramic powder as a partial replacement of cement and/or sand in cement pastes and mortars. Two different ceramic powders, featuring different grain-size distributions, have been employed, one from crushed bathroom fixtures and dental prosthesis waste and a second one from foundry industry residuals. With reference to cement pastes and mortars formulated from SCC mixes employed in precast industry, cement replacement volume percentages equal to 10 and 30% have been considered for each powder. The possibility of hybrid cement and sand replacement with either powder has also been addressed. Effects of the replacement on the workability, shrinkage, compressive and flexural strengths have been considered, up to 3 months curing. The results confirmed the possibility of using this kind of waste in concrete, thus reducing the demand for raw cement and the burden on disposal landfills.